2013
DOI: 10.1021/ar400106u
|View full text |Cite
|
Sign up to set email alerts
|

B═B and B≡E (E = N and O) Multiple Bonds in the Coordination Sphere of Late Transition Metals

Abstract: Because of their unusual structural and bonding motifs, multiply bonded boron compounds are fundamentally important to chemists, leading to enormous research interest. To access these compounds, researchers have introduced sterically demanding ligands that provide kinetic as well as electronic stability. A conceptually different approach to the synthesis of such compounds involves the use of an electron-rich, coordinatively unsaturated transition metal fragment. To isolate the plethora of borane, boryl, and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 53 publications
1
41
0
1
Order By: Relevance
“…A similar comparison is made for the double-bond and triplebond cases in Tables 3 and 4 21 for LiRb and KCs, respectively, in adequate agreement. We repeat here that the r 1 (Cs) of "253 pm", given in certain sources, seems to be a perpetuated misprint of an earlier value of 235 pm, 22 29 Si−Cl Bonds Short. As discussed by Wells 18 in 1949, they are "short".…”
Section: Introductionmentioning
confidence: 60%
“…A similar comparison is made for the double-bond and triplebond cases in Tables 3 and 4 21 for LiRb and KCs, respectively, in adequate agreement. We repeat here that the r 1 (Cs) of "253 pm", given in certain sources, seems to be a perpetuated misprint of an earlier value of 235 pm, 22 29 Si−Cl Bonds Short. As discussed by Wells 18 in 1949, they are "short".…”
Section: Introductionmentioning
confidence: 60%
“…17 In contrast to noncluster boryls, the exohedral metal–boron bonds in the majority of icosahedral carborane complexes are generally considered to be stable due in part to the strong steric shielding provided by the boron cage. We hypothesized that the highly strained, electron-rich, 3a Ru–B bonds in the (BB)-carboryne 2 can themselves serve as nucleophilic reaction centers, thus diverging from the other B-carboranyl complexes (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the transition metal iminoboryl systems were found to be stable against oligomerization, yet reactive towards a variety of substrates. [6,7] In recent years, it has been shown that stable singlet carbenes [8] can be used, in place of transition metals, to not only stabilize a variety of highly reactive species, [9] but also to activate small molecules and enthalpically strong bonds. [10,11] Herein, we report that a singlet cyclic (alkyl)(amino)carbene (CAAC) [12] reacts with bis(trimethylsilyl)dihaloboranes, and allows for the preparation of room-temperature-stable iminoboryl-carbene adducts.…”
Section: Introductionmentioning
confidence: 99%